Kariera jako domena hierarchizująca przestrzeń społeczną – perspektywa funkcjonalno-strukturalna - Cybal-Michalska , Agnieszka (Studia Edukacyjne, 2020)
The tradition positioning the study of careers in the structural-functional orientation sees the career as an external system, an objective phenomenon. In this cognitive perspective, a career means a sequence of professional roles fulfilled by the subject, which could mean promotion, stability or degradation. If we adopt an objective criterion to distinguish careers, it would be the positions (professional position or position within the profession) occupied in formal structures. In this sense, a career is not the attribute of an individual, but is the property of the professional role.